ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS DALAM MENGUKUR KINERJA KEUANGAN PT. PUTRA WAJO KOLAKA PERIODE 2021-2024 - Faiz, Faiz; Sabarudin, Sabarudin; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
: This study applies data analysis techniques that involve evaluating liquidity ratios—namely the current ratio, quick ratio, cash ratio, and cash turnover—as well as solvency ratios such as the debt to asset ratio, debt to equity ratio, and long-term debt to equity ratio. The findings reveal that the company’s liquidity performance is generally strong, as reflected in an average current ratio of 1.87 times (considered good), a quick ratio of 1.27 times (less satisfactory), a cash ratio of 72% (very strong), and a cash turnover rate of 35% (very strong). On the other hand, solvency performance shows varied results, with the debt to asset ratio averaging 55% (very strong), the debt to equity ratio at 56% (moderately weak), and the long-term debt to equity ratio at 57% (very strong). Based on the overall analysis, it can be inferred that PT Putra Wajo Kolaka’s financial condition during the review period is relatively stable and sound in terms of both liquidity and solvency. Nevertheless, attention should be given to improving the quick ratio and debt to equity ratio, as these metrics still reflect less optimal outcomes, potentially posing financial risks in the future. This research aims to offer useful insights for company leadership in enhancing financial decision-making and to act as a reference point for future related studies. Keywords: Liquidity, Solvency, Financial Performance